ANALYSIS OF IMPROVING THE PERFORMANCE OF BOYOLALI DPRD MEMBERS DURING THE 2021 PANDEMIC - Ali Hufroni; Denny Asmara; Afiefah Sulistyowati; Sudarwati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
The purpose of this study is to determine whether there is a significant influence between the variables of flexibility, IT utilization, motivation, and work discipline on employee performance. In addition, it is also to find out whether there is a significant simultaneous influence and which variables are the most dominant in influencing employee performance in members of the Sukoharjo Regency DPRD. The method used is a quantitative descriptive method. The population in this study was 44 members and the entire population was sampled in this study, where the sampling technique used quota sampling. The data used are primary data and secondary data with data collection techniques: observation, documentation, questionnaires and literature studies. The data analysis technique in this study used multiple linear tests. The results of the study can be concluded that:: 1) There is an influence of flexibility, the use of IT, motivation, and work discipline have a simultaneous effect on performance in members of the Boyolali Regency DPRD, 2) There is an influence of flexibility on performance on members of the Boyolali Regency DPRD, 3) There is an influence of IT utilization on performance in members of the Boyolali Regency DPRD, 4) There is an influence of motivation on performance in members of the Boyolali Regency DPRD, 5) There is an influence of work discipline on performance on members of the Boyolali Regency DPRD Keywords : employee performance, flexibility, IT utilization, motivation, work discipline